Anteriomedial Access Regional Sciatic Nerve Block - V. G. Pechersky; A. V Marochkov; A. N. Bordilovsky (Общая реаниматология, 2011)
Anteriomedial-access regional sciatic nerve block has been devised and applied. Thirty-five anteriomedial-access regional sciatic nerve blocks were performed in the supine position, by using ultrasound imaging and electrostimulation of the peripheral nerves. The anteriomedial approach to the sciatic nerve permits anesthesia to be made without changing the body position in patients with multiple lower limb fractures and traumatic upper limb injury. More potent premedication was used during manipulation, by achieving a Ramsay sedation scale score of 3—5. The anesthesia was effective in all cases. There were no complications. Key words: regional anesthesia, sciatic nerve, anteriomedial access, ultrasound imaging.